Historia wyższego szkolnictwa muzycznego – wybrane wymiary i dążenie do profesjonalizacji - Kędzia, Marta (Biuletyn Historii Wychowania, 2026)
Polish public music schools, subordinated to the Ministry of Culture and National Heritage, currently serve as scientific and artistic centres and educate future musicians, teachers, composers, conductors and music theoreticians, as well as conduct research and artistic activities, contributing to the development and promotion of musical culture in Poland and abroad. The aim of this article is to present selected facts from the history of eight state music schools currently operating in Poland, listed on the list of art schools on the website of the Ministry of Culture and National Heritage. The study was presented in the context of the historical and political reality of Poland in the 19th and 20th centuries. The source of information about the history of music universities in Poland are materials posted on the websites of music universities and artistic institutions, as well as scientific publications on the development of music education. Statistical studies from the period of the Second Polish Republic and articles describing the development of the concept of Polish music education were also written on this topic.